(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Folk literature of Goalpara district is a complete literature. The district is inhabited not by a particular group of people, but by people of different groups. They are Bodos, Rabhas, Rajbanshis, Garos, Konches, Brahmins, Kalitas, Jogis, Kaibarttas, Namo Sudras, and Muslims (in later years) etc. Each of the above named group of people has their individual culture and literature. They have common literature also. All the cultures are old and traditional. They are rich and racy. GoalparianFolk literature can easily claim an honourable place in the world literature platform. For that work an ardent, strong and continuous attempt is essentially needed. Goalparian Folk literature is complete in itself. With affirmation it can be said that Goalparian literature can complete any literature of the world. But its hopeful publications and propagations are not satisfactory. Goalparian Folk literature includes (i) Hymns, (ii) Songs relating to agriculture, (iii) Marriage Songs, (iv) ‘ Nam ‘ Songs, (v) Bihu Songs, (vi) Juvenile Songs and dances, (vii) Mantra Songs, (viii) Healing Songs, (ix) Dances, (x) Santankamana Geets, (xi) Tales, (xii) Stories, (xiii) Nature’s Beauty—blessings, (xiv) Maxims, (xv) Boat man’s Geet, (xvi) Dehatattba Geets, (xvii) Cowherd’s Geets etc. After all Folk literature of Goalpara District has a good place. It is part and parcel of Assamese literature.